2011
DOI: 10.1007/s00394-011-0237-9
|View full text |Cite
|
Sign up to set email alerts
|

Four-week ingestion of blood orange juice results in measurable anthocyanin urinary levels but does not affect cellular markers related to cardiovascular risk: a randomized cross-over study in healthy volunteers

Abstract: Following supplementation of healthy volunteers with 1 L/day of blood OJ for 4 weeks, the ACN plasma levels reached were insufficient to significantly modify cell markers of platelet and leukocyte activation and interaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 28 publications
(32 reference statements)
0
19
0
2
Order By: Relevance
“…Previously, whole powdered black raspberry supplementation did not prevent the development of obesity or improved lipid status in HFD mice [19] and it was suggested that complex glycosylation nature of black raspberry anthocyanins precluded their ability to modulate metabolic health [36]. A similar observation was made for complex acylated cyanidins from purple carrot [14], diglycosylated cyanidins from elderberry [12], acylated and diglycosylated cyanidins from blood orange [13], and monoglycosylated cyanidins from jaboticaba [37]. Weak antidiabetic effects were reported in animals for cyanidins from purple corn [38], black soybeans [39], purple sweet potato [40], mulberry [41], cherry [42], chokeberry [43] or highly purified cyanidin-3-glucoside alone [44].…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…Previously, whole powdered black raspberry supplementation did not prevent the development of obesity or improved lipid status in HFD mice [19] and it was suggested that complex glycosylation nature of black raspberry anthocyanins precluded their ability to modulate metabolic health [36]. A similar observation was made for complex acylated cyanidins from purple carrot [14], diglycosylated cyanidins from elderberry [12], acylated and diglycosylated cyanidins from blood orange [13], and monoglycosylated cyanidins from jaboticaba [37]. Weak antidiabetic effects were reported in animals for cyanidins from purple corn [38], black soybeans [39], purple sweet potato [40], mulberry [41], cherry [42], chokeberry [43] or highly purified cyanidin-3-glucoside alone [44].…”
Section: Discussionmentioning
confidence: 77%
“…However, anthocyanins from different plants show various degrees of hydroxylation, methylation, glycosylation, and acylation [16]. This may explain the equivocal results from animal and human studies, since predominantly delphinidin- and malvidin-containing fruits are more likely to improve metabolic and cardiovascular risk factors (i.e., blueberry [6], black currants and bilberry [9,10], or grapes [11]), while cyanidins offer less protection (i.e., elderberry [12], blood orange [13], or purple carrot [14]). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the intake of red grape juice rich in anthocyanin reduced the concentrations of oxidized LDL and the activity of NADPH oxidase in dialysis patients [63], and the inhibitory effects of fruits containing anthocyanins on atherosclerosis were reported in elderly men [64]. Recent studies, however, showed no effects of blackcurrant juice [65] and blood orange juice [66] on cardiovascular risk markers.…”
Section: Cvdmentioning
confidence: 94%
“…In addition, activation of circulating inflammatory cells, such as polymorphonuclear (PMN) leukocytes and monocytes, membrane expression of adhesion molecules involved in their interaction with platelets and endothelial cells and the release of oxidation products may play a pathological role in the development of atherogenesis and thrombosis [11]. Moreover, lipoproteins have been shown to induce the release of bioactive compounds, such as cytokines, nitric oxide and reactive oxidative species, affecting cell systems of the vascular wall, blood pressure and hemostasis [12]. The aim of this study was to evaluate in healthy volunteers the effect of two types of orange juice, either poor or rich in anthocyanins (a largely represented class of polyphenols, responsible for the blue, red and purple colors of many fruits, vegetables and grains present in the Mediterranean diet) on the modifications induced by a fatty meal on peripheral blood cells and on the endothelial function.…”
Section: Introductionmentioning
confidence: 99%